Manajemen Pengelolaan Santri Mahasiswa - Sunardi, Sunardi; Munfarida, Isah; Mujahidin, Mujahidin; Zaini, Fawaidul (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research aims to analyze the management of student students at the Al-Urwatul Wutsqo Islamic Boarding School Jombang, which integrates religious education and formal education in higher education. The approach used in this research is descriptive-qualitative, with data collection techniques through interviews, observation, and documentation. The research focus includes planning, organizing, implementing, and evaluating the management of student students. The research results show that the management of student students at the Al-Urwatul Wutsqo Islamic Boarding School is carried out systematically by applying the principles of Islamic boarding school-based education management. Apart from that, the synergy between the religious and academic curriculum has succeeded in creating a conducive learning environment, improving the quality of learning, and supporting students' character development. However, this research also found challenges in providing facilities and infrastructure and managing time between academic activities and Islamic boarding schools. It is hoped that the implications of this research can contribute to the development of educational management in Islamic boarding schools in a more effective and sustainable way.